Use of gliptins reduces levels of SDF-1/CXCL12 in bullous pemphigoid and type 2 diabetes, but does not increase autoantibodies against BP180 in diabetic patients - Nätynki, Antti; Leisti, Päivi; Tuusa, Jussi; Varpuluoma, Outi; Huilaja, Laura; Izumi, Kentaro; Herukka, Sanna-Kaisa; Ukkola, Olavi; Junttila, Juhani; Kokkonen, Nina; Tasanen, Kaisa (Frontiers in Immunology, 2022)
The use of dipeptidyl peptidase 4 (DPP4) inhibitors, (also known as gliptins), is associated with an increased risk of bullous pemphigoid (BP), an autoimmune blistering skin disease. To explore the mechanism behind gliptin-associated BP we investigated circulating autoantibodies against the major BP autoantigen BP180 in serum samples from patients with type 2 diabetes (T2D) with preceding gliptin medication (n = 136) or without (n = 136). Sitagliptin was the most frequently prescribed gliptin (125/136 patients). Using an ELISA assay, we showed that IgG autoantibodies against the immunodominant NC16A domain of BP180 were found in 5.9% of gliptin treated and in 6.6% of non-gliptin treated T2D patients. We found that 28% of gliptin treated patients had IgG autoantibodies recognizing the native full-length BP180 in ELISA, but among non-gliptin treated the seropositivity was even higher, at 32%. Further ELISA analysis of additional serum samples (n = 57) found no major changes in the seropositivity against BP180 during a follow-up period of about nine years. In immunoblotting, full-length BP180 was recognized by 71% of gliptin treated and 89% of non-gliptin treated T2D patients, but only by 46% of the age-and sex-matched controls. The chemokine stromal derived factor-1(SDF-1/CXCL12) is one of the major substrates of DPP4.